2019
DOI: 10.12669/pjms.36.2.1284
|View full text |Cite
|
Sign up to set email alerts
|

Dentin bond strength of bioactive cement in comparison to conventional resin cement when photosensitized with Er,Cr:YSGG Laser

Abstract: Objective: The purpose of the present study was to assess dentin shear bond strength (SBS) and mode of bond failure of bioactive cement (BA) in comparison to conventional resin cement when photosensitized by Er,Cr:YSGG Laser (ECL). Methods: The present in-vitro study was carried out from March 2019 to May 2019. Sixty permanent non-carious, intact, non-fractured molars were isolated and mounted vertically in acrylic resin. Buccal surface of each molar tooth was ground, polished and surface treated with EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…1 An intimate bond between the adhesive and dentin certifies that the resin composite material would bear the adversities of the dynamic oral environment (temperature and pH fluctuations). 2 To improve the mechanical properties of dentin adhesives, researchers have tried various strategies. 3 One of the approaches is to incorporate bioactive inorganic fillers in the adhesive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 An intimate bond between the adhesive and dentin certifies that the resin composite material would bear the adversities of the dynamic oral environment (temperature and pH fluctuations). 2 To improve the mechanical properties of dentin adhesives, researchers have tried various strategies. 3 One of the approaches is to incorporate bioactive inorganic fillers in the adhesive.…”
Section: Introductionmentioning
confidence: 99%
“…9 Formerly, calcium-fluoride (CaF 2 ) particles have been added to various dental materials like pit and fissure sealants, glass ionomer cement (GIC), and adhesives with encouraging results. 5,11,12 A previous study used CaF 2 nanoparticle fillers in the adhesive and reported remineralization of caries-affected dentin. 13 In another study, Mitwalli et al also witnessed and demonstrated that CaF 2 containing nanocomposites revealed resilient antibacterial and ion releasing properties without any significant effect exerted on the material's mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…28 Moreover, this type of failure mode is also related to type of substrate, method of SBS testing and mode of conditioning method. 1012 In addition, debonded samples in group 3, 4, 5, 7 and 8 exhibited cohesive and admixed failure types. Available evidence suggests better adhesion is associated with high repair bond values and this method of failure.…”
Section: Discussionmentioning
confidence: 94%
“…8,9 Therefore, a direct repair of such restorations has to be considered as a more viable option. The repair procedure involves surface treatment of the fractured ceramic interface to create roughness through mechanical means to increase surface area, such as air abrasion (AA); laser irradiation 2,[10][11][12][13] or chemical means to increase the wettability for bonding, by acid etching with hydrofluoric acid (HFA) and bonding with Silane coupling agents. 2,14,15 The treated surface is then ready to receive an adhesive composite resin material to restore the defect.…”
Section: Introductionmentioning
confidence: 99%
“…It also provides a comparative analysis with other investigational groups. 14 In the present study, two different classes of photosensitizers were assessed. MBP and TB from class Phenothiazinium whereas, CP and P from natural class photosensitizers.…”
Section: Discussionmentioning
confidence: 99%